2020
DOI: 10.1289/ehp6578
|View full text |Cite
|
Sign up to set email alerts
|

The International Society for Children’s Health and the Environment Commits to Reduce Its Carbon Footprint to Safeguard Children’s Health

Abstract: The Lancet Countdown and the 2018 Intergovernmental Panel on Climate Change declared that the worst impacts of climate change are and will continue to be felt disproportionately by children. Children are uniquely vulnerable to the consequences of climate change, including heat stress, food scarcity, increases in pollution and vector-borne diseases, lost family income, displacement, and the trauma of living through a climate-related disaster. These stressors can result in long-lasting physical and mental health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 31 publications
(26 reference statements)
0
10
0
1
Order By: Relevance
“…Anaesthetists and critical care physicians should be aware of the benefits of teleconferencing on the environment and health, 143 and also on academic and administrative meetings. 144 , 145 …”
Section: Travelmentioning
confidence: 99%
“…Anaesthetists and critical care physicians should be aware of the benefits of teleconferencing on the environment and health, 143 and also on academic and administrative meetings. 144 , 145 …”
Section: Travelmentioning
confidence: 99%
“…This is only possible by way of a self-imposed cap on academic emissions. For instance, The International Society for Children’s Health and the Environment recently committed to reducing its air travel by 20% ( 8 ). Other authors have recommended a commitment by academic institutions to reduce travel by 5% per year, similar to sectoral and national carbon cap schemes.…”
Section: The Contribution Of Air Travel To Carbon Emissionsmentioning
confidence: 99%
“…Young people will live much of their lives on an earth whose conditions are increasingly altered by climate change. Various dimensions of their lives, including their security, well-being, and even mental health, will be negatively affected by climate change [11]. Recent studies have shown how climate change and extreme weather events have negatively affected the physical and mental health conditions of young people, including children [12][13][14].…”
Section: Introductionmentioning
confidence: 99%